The Roots and Development of Particle Physics in India - Raychaudhuri, Sreerup. author. aut Link
VIII, 138 p. 4 illus.
Keywords: This book narrates the history of the initiation and development of elementary particle physics in India and by Indians, focusing on the first half of the twentieth century. The thread is taken up with the introduction of Western science into India in the previous century. The contents are a mixture of science and biographies, interspersed with anecdotes and reflections on the historical and societal connections. The style is generally non-technical, with any technical issues explained and interwoven into the narrative. This book is of interest to scientists, to people with interest in science and the history of science, students curious about the initiation of science in the Indian context and about the famous Indian scientists, as well as administrators who wish to understand the roots of current Indian science, especially in the context of particle physics.